2001
DOI: 10.1038/ng716
|View full text |Cite
|
Sign up to set email alerts
|

Hypotrichosis with juvenile macular dystrophy is caused by a mutation in CDH3, encoding P-cadherin

Abstract: Congenital hypotrichosis associated with juvenile macular dystrophy (HJMD; MIM601553) is an autosomal recessive disorder of unknown etiology, characterized by hair loss heralding progressive macular degeneration and early blindness. We used homozygosity mapping in four consanguineous families to localize the gene defective in HJMD to 16q22.1. This region contains CDH3, encoding P-cadherin, which is expressed in the retinal pigment epithelium and hair follicles. Mutation analysis shows in all families a common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 12 publications
4
143
1
3
Order By: Relevance
“…Recent advances in molecular genetics have revealed that two recessively inherited human diseases, HJMD and EEM syndrome, are caused by mutations in the CDH3 gene, encoding P-cadherin (Sprecher et al, 2001;Kjaer et al, 2005). In this study, we identified five consanguineous Pakistani families (Families 1-5) affected with either HJMD or EEM syndrome and found mutations in the CDH3 in all five families.…”
Section: Discussion P-cadherin Mutations Cause Hjmd or Eem Syndrome Imentioning
confidence: 97%
See 2 more Smart Citations
“…Recent advances in molecular genetics have revealed that two recessively inherited human diseases, HJMD and EEM syndrome, are caused by mutations in the CDH3 gene, encoding P-cadherin (Sprecher et al, 2001;Kjaer et al, 2005). In this study, we identified five consanguineous Pakistani families (Families 1-5) affected with either HJMD or EEM syndrome and found mutations in the CDH3 in all five families.…”
Section: Discussion P-cadherin Mutations Cause Hjmd or Eem Syndrome Imentioning
confidence: 97%
“…9). Nevertheless, in HJMD families, all affected individuals have hair and eye involvement only (Sprecher et al, 2001;Indelman et al, 2002;Indelman et al, 2003;Indelman et al, 2005;Indelman et al, 2007). Similarly, in EEM families, all affected individuals show not only hair and eye phenotype but also hand/foot involvement (Kjaer et al, 2005).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…CDH3 gene mutations have been shown to cause P-cadherin functional inactivation, leading to developmental defects associated with two inherited diseases in humans: 1) hypotrichosis with juvenile macular dystrophy (HJMD) and 2) ectodermal dysplasia, ectrodactyly, and macular dystrophy (EEM syndrome). The common features of both diseases are sparse hair and macular dystrophy of the retina, while only EEM syndrome shows the additional finding of split hand/foot malformation (SHFM) (Kjaer et al, 2005, Sprecher et al, 2001. No defects were described for these conditions, concerning the human mammary development, or other epithelial bud structures.…”
Section: B Amentioning
confidence: 99%
“…Alternatively, disrupted adhesion between P-cadherin-negative myoepithelial cells might allow access of epithelial cells to the basement membrane and signals it might initiate. A human mutation in the P-cadherin gene producing a truncated, nonmembrane bound protein results in eye and hair defects, but no reported mammary gland abnormalities [Sprecher et al, 2001]. P-cadherin may play a role in the mammary gland besides providing an adhesion mechanism to the myoepithelium.…”
Section: Cadherins and Catenins In The Normal Mammary Glandmentioning
confidence: 99%